Hahnemann's Organon Alive in Practice - Shukla, Chetna N. (Homœopathic Links, 2018)
‘When the student is ready the teacher will appear’. This saying is attributed to Buddha Siddhartha Gautama Shakyamuni and the Theosophists. This case is a proof for me for a quote I would like to formulate ‘When the sick is ready to heal the remedy will appear’. The all-wise preserver of human life works its miracles unconditionally to assist the sick to restore health. Uniqueness surrounds this case. When I treated this boy with alopecia I only had the 30th CK potency that I had potentised. This was the potency that also completed the cure. The emphasis of this article is to elicit §14 and 138 in my practice during the proving of Hippocampus kuda that I conducted in 1996. Since then during some of my provings I witnessed them come alive. The most recently was during the proving of the blood of Indian grey mongoose in July 2016.
Keywords: organon of medicine; §14; visible morbid alteration; §138; accidents; proving; Hippocampus kuda; alopecia; Lac equinum; Chamomilla vulgaris; Aloe